Implementasi Kebijakan Pengembangan Kompetensi Aparatur Sipil Negara Di Kabupaten Sumenep - Haris, Rillia Aisyah (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
Policy reform in the development of state civil apparatus competence is the government's commitment to continuously make improvements in the management of civil state apparatus. It aims to produce the optimal performance of the state civil apparatus. Especially in performing public service duties. The commitment is marked by the enactment of Law No. 5 of 2014 on State Civil Apparatus. This study aims to determine the implementation of apparatus competency development policy in Sumenep regency. The research method used is qualitative with descriptive approach. The focus of this research emphasizes the implementation model of Edward III covering communication, resources, disposition, and bureaucratic structure. The result of the research shows that implementation of apparatus competency development policy in Sumenep regency has been implemented effectively.DOI:Â https://doi.org/10.26905/pjiap.v2i2.1928